Lipid Assemblies at the Crossroads of Aging, Proteostasis, and Neurodegeneration. Issue 12 (December 2019) - Roitenberg, Noa; Cohen, Ehud
Abstract : The proteostasis network (PN) is a nexus of mechanisms that act in concert to maintain the integrity of the proteome. Efficiency of the PN declines with age, resulting in the accumulation of misfolded proteins, and in some cases in the development of neurodegenerative disorders. Thus, maintaining an active and efficient PN through the late stages of life could delay or prevent neurodegeneration. Indeed, altering the activity of aging-regulating pathways protects model organisms from neurodegeneration-linked toxic protein aggregation. Here, we delineate evidence that the formation and integrity of lipid assemblies are affected by aging-regulating pathways, and describe the roles of these structures in proteostasis maintenance. We also highlight future research directions and discuss the possibility that compounds which modulate lipid assemblies could be used for the treatment of neurodegenerative disorders. Highlights: The proteostasis network (PN) is a nexus of mechanisms that maintain the integrity of the proteome. The competence of the PN declines with age, exposing the cell to protein toxicity and the organism to conformational diseases including neurodegenerative disorders. Neurodegenerative disorders such as Alzheimer's disease, are late-onset conformational maladies. The IGF1 signaling cascade is an aging-regulating pathway whose knockdown alters the progression of aging and protects model organisms from disease-associated phenotypes. Among other effects, the knockdown of IGF1 signaling modulates protein contents of lipid assemblies. Lipid assemblies serve as scaffolds for the organization and function of signaling complexes and play important roles in the maintenance of proteostasis.